Edukasi Pemanfaatan Limbah Plastik untuk Anak Usia Dini - Indah Rahayu Lestari; Ravindra Safitra Hidayat; Hakam Ali Niazi; Rinny Meidiyustiani; Heni Iswati; Nora Andira Brabo (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
The icreasing pollution resulting from plastic waste, not only on land, but also can disturb of ecosystem. It can take 500 years to decompose plastic used for mineral bottles. By utilizing plastic waste, it hoped that can contribute to save the environment. By introduction plastic materials, it hoped that early childhood will be more aware of the environment. Children are invited to be creative using plastic bottles to make saving containers. In addition to inviting children to learn to use plastic waste, it also can introduces children to learning to save at an early age. With creation made by children, it hoped that children will be aware of the environment, children will take part in saving the environment and reducing the use of the environment, children will take part in saving the environment and reducing the use of plastic waste.